Peluang dan Tantangan Pengembangan Industri Kreatif Kuliner dalam Pencapaian SDGs - Faturachman Alputra Sudirman; Fera Tri Susilawaty; Aenal Fuad Adam (Universitas Musamus, Merauke, Papua, 2020)
The creative industry is one of the industries that are able to contribute to the regional economy, and oneof the creative industries sub-sectors that can become leading creative industries is the culinarysubsector. The existence of this industry is also aligned to achieve the agenda of sustainable developmentgoals (SDGs) on the 8th goal related to sustainable and inclusive economic growth. But for specificregions, the existence of the creative culinary industry has challenges in its development. This study aimsto discuss the opportunities and challenges of developing a creative culinary industry in Kendari Cityand their contribution to the achievement of SDGs. The research method used is a qualitative researchmethod using interviews and documentation of data collection techniques. The findings in this studyindicate that the opportunities for culinary creative industry development are triggered by the growth ofentrepreneurial interest and creativity of industry players, this has gained momentum because it is drivenby culinary trends as lifestyle and leisure, as well as government support programs in culinarydevelopment itself. As for the challenges faced, such as venture capital, licensing, andplace/business space for the development of creative culinary industries. However,overall the existence of the creative culinary industry in the city of Kendari was able tosupport the achievement of SGDs 2030 on the goal 8 to create jobs and absorb youngworkers.